Characterization of Arbequina virgin olive oils produced in different regions of Brazil and Spain: physicochemical properties, oxidative stability and fatty acid profile - Borges, Thays H. (2016)
Production of virgin olive oil is beginning in Brazil. This paper analyzes the characteristics of the EVOO Arbequina from Brazil in comparison with Spanish Arbequina from different regions. Quality parameters, oxidative stability, pigments, colour and fatty acid profile were assessed, and relationships with geographic and climatic conditions were studied. All the samples presented good quality and met EU standards for extra-virgin olive oil, but there were significant differences between regions and countries for many of the parameters evaluated. Major differences between Brazilian and Spanish samples were observed for free acidity and colour of the oils, as well as minor variations in the fatty acid profile. The colour differences were related to rainfall, whereas the fatty acid content was strongly influenced by altitude and temperature. These results highlight the fact that geographic area and environmental factors influence the characteristics of Arbequina oil and play an important role in newly introduced cultivars.